Forecasting Number of Passengers of TransJakarta using Seasonal ARIMAX Method - Maftukhatul Qomariyah Virati; Diory Paulus Pamanik; Setia Pramana (Journal of Data Science and Its Applications, 2020)
TransJakarta is one of the most common public transportation modes used by the public in Jakarta. Every day there are more than 300.000 people who use TransJakarta . The number of TransJakarta buses is still limited, so to optimize services, we should know when the number of users in peak time and when the number of users in low time. In addition to providing comfort to customers, maintenance for TransJakarta buses can also be optimized, thereby reducing incident and unwanted events. This study investigates the pattern of the number of TransJakarta passengers differs on weekends, weekdays, and holidays. Also, this study predict how many TransJakarta passengers in the future, by using SARIMAX method, which is SARIMA method with X - factor. In the implementation, the study is conducted using R application with the addition of x-factor in the form of dummy variable for tap-in data in holiday period.The predicted result being produced is not too far away with the actual figure with the best model is SARIMA(0,0,0)(2,1,0)[7] with x-factor and the error analys is MSE = 162402173, MAPE = 2.6122 and MASE = 0.211698.